Defining Elemental Imitation Mechanisms: A Comparison of Cognitive and Motor-Spatial Imitation Learning Across Object- and Computer-Based Tasks. Issue 2 (14th March 2016) - Subiaul, Francys; Zimmermann, Laura; Renner, Elizabeth; Schilder, Brian; Barr, Rachel
Abstract : During the first 5 years of life, the versatility, breadth, and fidelity with which children imitate change dramatically. Currently, there is no model to explain what underlies such significant changes. To that end, the present study examined whether task-independent but domain-specific—elemental—imitation mechanism explains performance across imitation tasks or domains. Preschool-age children ( n = 156) were tested on 4 imitation tasks, 2 object-based (animal, puzzle box) and 2 computer-based (cognitive, motor-spatial). All tasks involved 3 serial actions. The animal task involved making an animal face, and the puzzle box task involved manipulating a box to retrieve a reward. The cognitive task involved responding to 3 different pictures in a specific picture order, and the motor-spatial task involved responding to 3 identical pictures in a specific spatial order. A principal component analysis including performance on all 4 tasks produced 2 components: "cognitive imitation" (cognitive and animal tasks) and "motor-spatial imitation" (motor-spatial and puzzle box tasks). Regression analyses replicated these results. These findings provide preliminary support for the hypothesis that underlying performance across these different tasks involves multiple—elemental—imitation mechanisms for learning and copying domain-specific information across tasks.